Banks and the Finnish credit cycle 1986-1995 - Vesa Vihriälä (Bank of Finland, 1997)
The study focuses on the role of deposit banks in the makings of the Finnish credit cycle of 1986-1995.A preliminary descriptive analysis suggests that banks' credit supply had a positive effect on credit growth in the boom period and a negative effect in the early 1990s.There are furthermore some indications that moral hazard of weak banks played a role in the expansion phase and that insuffient capital constrained lending later on, thus causing a credit crunch. A theoretical model set up here suggests that one should examine the effects of both bank capital and costs on lending and also look at the issuance of subordinated debt as a means of testing the moral hazard and credit crunch hypotheses. An empirical analysis of the behaviour of 483 cooperative and savings banks over the second half of the 1980s gives strong support to the moral hazard hypothesis.In particular, the aggregate credit supply of the savings banks would have been substantially less if their capital had been high enough to eliminate moral hazard incentives. By contrast, almost no evidence of a credit crunch induced by weak bank capital is found in an analysis of 313 cooperative and savings bank in 1991 and 1992.Instead the effects of borrower creditworthiness and credit demand are underlined.
URN:NBN:fi:bof-201408071676
Keywords: 330; credit crunch; moral hazard; capital regulation; banking crisis